Severity of Work Disability and Work - Oguzoglu, U (My University, 2009)
This paper analyzes the effect of severity of disability on labour force participation by using a self-reported work limitation scale. A dynamic labour force participation model is used to capture the feedback effect of past participation on current participation. The results suggest that net of persistence and unobserved heterogeneity, differences in severity levels explain a significant portion of the variance in the participation rates among disabled individuals. Moreover, the disability is shown to have longer lasting adverse effects on female participation and work limited women will be more likely to benefit from the work requirements imposed on Disability Support Pension recipients.
IZA Discussion Paper
Keywords: Employment; Health -- Disability; Employment -- Labour force participation; Health; Health and wellbeing; Labour market; Health; Employment and unemployment